Atividade das enzimas ntpdase, 5´-nucleotidase e adenosina deaminase em plaquetas de ratos infectados por Trypanosoma evansi - Oliveira, Camila Belmonte (2010)
Nucleotide- and nucleoside-degrading enzymes are present in the surface of platelets, blood cells involved in clotting disturbances of Trypanosoma evansi-infected animals. Thus, this study was aimed at evaluating the activity of the enzymes NTPDase, 5 - nucleotidase and adenosine deaminase in platelets of rats experimentally infected by T. evansi. Animals were divided into four groups, according to the degree of parasitemia. Samples were collected at days 3 (group A: at the beginning of parasitemia), 5 (group B: high parasitemia) and 15 (group C: chronic infection). Group D (control group) was composed of non-infected animals. Blood samples with citrate as the anticoagulant were collected and used for platelet separation and enzymatic assays. NTPDase, 5 - nucleotidase and adenosine deaminase (ADA) activities were decreased (p<0.05) in platelets from rats of groups A and B, when compared to the control group. In group C, only NTPDase and 5 -nucleoside activities were decreased (p<0.001), observed by ADP and AMP hydrolysis. The correlation between platelet count and nucleotide and nucleoside hydrolysis was positive and statistically significant (p<0.05) in groups A and B. Platelet aggregation of all infected groups was decreased in comparison to the control group (p<0.05). Based upon the results, it is concluded that the alterations observed in the activity of the enzymes NTPDase, 5 -nucleotidase and adenosine deaminase in platelets of T. evansi-infected animals might be related to thrombocytopenia.